Information and technology implementation issues in AAL solutions - Vardasca, Ricardo (2013)
With the population ageing effect, the technological developments, and pressure to reduce the cost with healthcare, are reunited the conditions for the development of Ambient Assisted Living (AAL) solutions. This work is a revision of the current state of the art. Its aim is the characterization of the AAL solutions, within the AAL4ALL scope. Therefore, it is presented features, scenarios and projects, referring the limitations and the opportunities for the future developments of prototypes using high level information and technology in AAL environments. Moreover, it is presented guidelines of operation, exposing the conceptual approach, and the discussion and conclusion, which present recommendations and current AAL4ALL project positions in terms of concepts and technologies.